MicroRNAs as potential biomarkers for monitoring of acquired sensorineural hearing loss - Yaqin Hu; Hongjiang Chen; Xiaoqing Zhou; Xiaoqin Luo; Zailan Tu; Jing Ke; Wei Yuan (Wiley, 2024)
Abstract Presbyacusis, sudden sensorineural hearing loss (SNHL), noise‐induced hearing loss, and drug‐induced deafness are the most common types of acquired SNHL. At present, the diagnosis of these hearing disorders is mainly based on the medical history and audiological examination. Due to the lack of diagnostic biomarkers, diagnosis of acquired sensorineural hearing loss is difficult. Previous studies have suggested that microRNAs (miRNAs) serve essential roles in pathophysiological processes, and they are stable, tissue enriched, and could be determined in a quantitative manner. Therefore, they could be potential noninvasive biomarkers for acquired SNHL. This review provided a comprehensive overview of the similarities and differences in altered circulating miRNAs (cimiRNAs) (plasma, serum, whole blood, and perilymph) in various disorders, and highlighted the regulatory functions of cimiRNAs on the development, monitoring and prognosis of the four most common types of acquired SNHL.